Tanzania Economic Update, February 2021 : Raising the Bar - Achieving Tanzania’s Development Vision - World Bank (World Bank, Washington, DC, 2021)
The emergency of the COVID-19 novel coronavirus plunged the global economy into a recession in 2020, and the pace of recovery remains uncertain both among advanced and emerging economies. Pandemic-related health restrictions and the adoption of precautionary behaviors by firms and consumers have greatly slowed economic activity, while uncertainty regarding the post-pandemic economic landscape and key policy decisions have discouraged investment. Agricultural and manufacturing firms face serious questions regarding the viability of global value chains, and the unforeseeable course of the pandemic weighs on international trade and tourism (World Bank 2021). Meanwhile, the disease itself continues to exact an enormous and mounting toll on human lives, and the disruption of education systems has slowed human capital accumulation, which could negatively impact the productivity of an entire generation. The global economy contracted by an estimated 4.3 percent in 2020, and while a 3.8 percent rebound is projected for 2021, worldwide economic output is expected to remain well below prepandemic trends over the near term.